2019
DOI: 10.1039/c9nj00369j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co addition on catalytic activity of FePCCu amorphous alloy for methylene blue degradation

Abstract: A novel FeCoPCCu amorphous alloy as a highly efficient catalyst in Fenton-like reactions for methylene blue degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Fe-based metallic glass catalysts (e.g., FeB, FeBC, FeBP, FeSiB, FePC, FeSiBCu, and FeNbSiB) feature high density of reactive sites due to the formation of local nanosized galvanic cells between different Fe-rich and Fe-poor atomic clusters, which promote the rapid degradation of dyes. [31][32][33][34][35][36][37][38][39] On the other hand, Fe-based high entropy alloys are typically made by mixing Fe with roughly equal amounts of multiple metallic elements, such as Cu, Co, Cr, Ni, Mn, etc. The resulting materials have been mainly exploited for dye decomposition through reductive pathways.…”
Section: New Conceptsmentioning
confidence: 99%
“…Fe-based metallic glass catalysts (e.g., FeB, FeBC, FeBP, FeSiB, FePC, FeSiBCu, and FeNbSiB) feature high density of reactive sites due to the formation of local nanosized galvanic cells between different Fe-rich and Fe-poor atomic clusters, which promote the rapid degradation of dyes. [31][32][33][34][35][36][37][38][39] On the other hand, Fe-based high entropy alloys are typically made by mixing Fe with roughly equal amounts of multiple metallic elements, such as Cu, Co, Cr, Ni, Mn, etc. The resulting materials have been mainly exploited for dye decomposition through reductive pathways.…”
Section: New Conceptsmentioning
confidence: 99%
“…Generally, reaction parameters such as catalyst dosage, pH, dye concentration, and H 2 O 2 concentration dominate the reaction efficiency in Fenton-like processes and an effective degradation of a dye solution usually involves the investigation of optimized parameters. For catalyst (metallic glass ribbons) dosage, most of studies have demonstrated that a higher dosage of catalyst generally contributes to a higher catalytic efficiency in AOPs [24,37,53,54]. Due to the heterogeneous catalyst nature, the use of excess metallic glass ribbons only results in supplementary additional surface active sites and the release of Fe 2+ from the ribbon surface by corrosion can be effectively controlled, which is different from the use of homogeneous Fe 2+ as catalyst leading to a scavenging effect on the produced radicals [41].…”
Section: Correlation Between Metallic Glasses and H 2 O 2 In Different Phmentioning
confidence: 99%
“…MB dye with a four-carbon ring, one nitrogen and one sulfur atom is classified as a thiazine dye and it is commonly used in medications [24,35]. Nowadays many researchers tend to employ MB dye as a classical organic pollutant example, since it is relatively stable at different pH values and solution temperatures, so as to investigate effect of AOPs using different catalysts [9,[36][37][38]. With triphenylmethane backbones, both crystal violet (CV) and malachite green (MG) dyes can be grouped as triarylmethane dyes with cationic charges and usually present intense color [39].…”
Section: Introductionmentioning
confidence: 99%
“…Near-rapid solidification with a cooling rate of 10 0 -10 3 °C s À1 has many advantages such as high solid-solubility, [1] fine structure, [2] less composition segregation, and existing metastable phase formation. [3][4][5][6][7] Liu Y.L. et al [8] have found that so many small intermetallics were precipitated and distributed in an Al-5Mg-1.4Mn alloy under near-rapid solidification.…”
Section: Introductionmentioning
confidence: 99%